The janitor’s knowledge and attitude towards household infectious waste countermeasure during pandemic COVID-19 in Manado city - Akili, Rahayu H.; Mandagi, Chreisye K. F.; Mahama, Corry N. (International Journal Of Community Medicine And Public Health, 2021)
Background: COVID-19 pandemic causes the emergence of rubbish indicated containing COVID-19 or usually called as infectious waste. The household waste sources related to COVID-19 prevention are such as ODP (people in observation) who had done self-quarantine and used APD (self protection equipment) such as mask and gloves. The purpose of this research is to find out the correlation between knowledge and attitude of janitor towards household infectious waste countermeasure during COVID-19 pandemic in Manado city 2020. Methods: This research was quantitative research-observational descriptive approach with cross sectional method. This research was conducted in 4 temporary shelters obtained in Singkil sub district, Bunaken sub district, Pall Dua sub district and Wanea sub district. The samples were selected by using total sampling technique. Total samples were 100 respondents. The research instrument was questionnaire. The analysis used Chi Square Test. Results: shows that the janitors’ knowledge is good already 53%, attitude 60%, and there is no correlation between knowledge and janitors’ attitude towards household infectious waste countermeasure during COVID-19 pandemic in Manado city. Conclusions: The management and countermeasure of household infectious waste is an important effort to prevent the transmission of SARS-CoV-12 (COVID-19). Tighter monitoring is necessary and also education/socialization of household infectious waste countermeasure is needed during COVID-19 pandemic either from the behavior side or the facilities used.